The Effect of Participative Leadership Style and the Implementation of Green Hotel Management on Environmental Performance - Arevin, Ayat Taufik (Research Horizon, 2024)
This study explores the effect of participative leadership style and the implementation of Green Hotel Management on environmental performance in Semarang hotels. In this context, leadership style plays an important role in directing and motivating employees to achieve organizational goals, especially in the implementation of green hotel programs. This quantitative study involved 150 hotel employees who had worked for one year, and used Structural Equation Modeling (SEM) with the help of AMOS 2.0 software to analyze the data. The results showed that participative leadership style and the implementation of green hotel management individually and simultaneously had a positive and significant influence on environmental performance. This finding is in line with previous studies showing that leadership that supports green programs and the implementation of green hotel practices can improve environmental performance. Based on these results, this study recommends that communication regarding green practices and cost implications should be carried out frequently to increase employee awareness, which can ultimately strengthen the success of implementing green hotels in Semarang.